CYP2J2 overexpression ameliorates hyperlipidemia via increased fatty acid oxidation mediated by the AMPK pathway. (5th June 2015) - Zhang, Shasha; Chen, Guangzhi; Li, Ning; Dai, Meiyan; Chen, Chen; Wang, Peihua; Tang, Huiru; Hoopes, Samantha L.; Zeldin, Darryl C.; Wang, Dao Wen; Xu, Xizhen
<x xml:space="preserve">Abstract</x> Objective The study aims to investigate the effect of cytochrome P450 2J2 (CYP2J2) overexpression on hyperlipidemia in mice and further to explore its effect on fatty acid oxidation in vivo and in vitro. Methods The effects and mechanisms of endothelial‐specific CYP2J2 transgene (Tie2‐CYP2J2‐Tr) on lipid and fatty acid metabolism were investigated in high‐fat diet (HFD) ‐treated mice. HepG2, LO2 cells, and HUVECs were exposed to 0.4 mM free fatty acid (FFA) for 24 h and used as a model to investigate the roles of CYP2J2 overexpression and epoxyeicosatrienoic acids (EETs) on fatty acid β‐oxidation in vitro. Results Tie2‐CYP2J2‐Tr mice had significantly lower plasma and liver triglycerides, lower liver cholesterol and fatty acids, and reduced HFD‐induced lipid accumulation. CYP2J2 overexpression resulted in activation of the hepatic and endothelial AMPKα, increased ACC phosphorylation, and increased expression of CPT‐1 and PPARα, which were all reduced by HFD treatment. In FFA‐treated HepG2, LO2, and HUVECs, both CYP2J2 overexpression and EETs significantly decreased lipid accumulation and increased fatty acid oxidation via activating the AMPK and PPARα pathways. Conclusions Endothelial‐specific CYP2J2 overexpression alleviates HFD‐induced hyperlipidemia in vivo. CYP2J2 ameliorates FFA‐induced dyslipidemia via increased fatty acid oxidation mediated by the AMPK and PPARα pathways.